2023
DOI: 10.3389/fpubh.2023.1243513
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet is associated with better gastrointestinal health and quality of life, and less nutrient deficiency in children/adolescents with disabilities

Hande Bakırhan,
Volkan Özkaya,
Merve Pehlivan

Abstract: BackgroundChildren and adolescents with disabilities face various nutritional problems. This study aimed to examine dietary characteristics, nutritional status and problems, gastrointestinal health, and quality of life in children and adolescents with disabilities.MethodsThis study included 5–18 years old children and adolescents (n = 1,991) with disabilities. We used the Mediterranean Diet Quality Index (KIDMED), the Gastrointestinal Symptom Rating Scale (GSRS), and the Pediatric Quality of Life Inventory (Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
2
0
1
Order By: Relevance
“…These results are in accordance with existing evidence that confirms the benefits of the Mediterranean diet for health in general and for the prevention of overweight [9,27,28]. Moreover, our findings highlight the significant association of family habits with children's health.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in accordance with existing evidence that confirms the benefits of the Mediterranean diet for health in general and for the prevention of overweight [9,27,28]. Moreover, our findings highlight the significant association of family habits with children's health.…”
Section: Discussionsupporting
confidence: 93%
“…An umbrella review conducted by Dinu and colleagues [28] revealed that increased adherence to the Mediterranean diet was linked to reduced risks of overall mortality, cardiovascular diseases, coronary heart disease, myocardial infarction, overall cancer incidence, neurodegenerative diseases, and diabetes. In another study conducted by Bakırhan and colleagues [27] involving a sample of 1991 children and adolescents with various physical or intellectual disabilities, it was concluded that greater adherence to the Mediterranean diet was associated with an improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de, até o momento, terem sido encontrados poucos estudos que investiguem o efeito da dieta mediterrânea em pacientes com TEA, a sua eficácia no tratamento do Transtorno de Déficit de Atenção e Hiperatividade (TDAH) indica que estudos neste sentido são bastante prósperos. 26…”
Section: Consequências De Uma Má Alimentaçãounclassified